Differential Responses of Capsicum Accessions to Foliar Blight and Root Rot by Phytophthora capsici - Kang, Won-Hee; Nam, Jae-Young; Kwon, Ji-Su; Yeom, Seon-In (Weon'ye gwahag gi'sulji, 2022)
The oomycete Phytophthora capsici is one of the most destructive pepper pathogens, reducingproduct quality and resulting in major yield losses in Capsicum spp. To date, little is known aboutthe defense responses of the host pepper against different P. capsici isolates. Although foliar blightand root rot are caused by the same pathogen, the host resistance responses may differ amongdisease symptoms and must be studied independently. In this study, 30 Capsicum accessions wereinoculated with two P. capsici isolates by root drenching, and the severity of root rot was evaluated. In addition, one P. capsici strain was injected into the leaves of the same 30 accessions to evaluatethe difference in host defense responses to foliar blight and root rot caused by the same strain. Among 30 accessions, 6 showed different resistance levels to the two P. capsici isolates. Whencomparing the resistance levels to root rot and foliar blight, 14 pepper accessions showed differentresistance responses based on the inoculation site. These results suggest that the resistance to foliarblight in peppers differs according to the isolate of P. capsici and the inoculation site, even withinthe same pepper cultivar. The results of this study will provide useful information for the breedingof Phytophthora root rot and foliar blight-resistant Capsicum peppers. KCI Citation Count: 3